Mewujudkan Negara Hukum Indonesia - Subechi, Imam (Jurnal Hukum dan Peradilan, 2012)
This Article entitled " the State law of Indonesian" is the result of a study on the conception of characteristic of law states of Indonesian that distinguish the conception of the state laws in other countries. Based on the research results, can be explained even get the effect of various thoughts, but conception of law state of Indonesian different with conception the rule of law and rechtsstaat. This can be search from basic of philosophy, the nature of sovereignty, the powers of state organs, and human rights. There are six main elements of Indonesian law states, namely: 1) Pancasila; 2) supremacy of law;; 3) democratic 4) restrictions and dispersal of state power; 4) independent judiciary; 6) protection of human rights. the statement of Indonesia as a democratic rule of law based on Pancasila then should all forms of civic and social action must be based on the law.Keywords: Pancasila, State of law (the rule of law, rechtsstaat), Democracy, Human Rights